2018
DOI: 10.21608/epsj.2018.17115
|View full text |Cite
|
Sign up to set email alerts
|

Improving Growth Traits and Estimating Heterosis, Additive and Maternal Effects a Cross Diallel Mating Among Three Lines Selected Heaviest Body Weight Under Heat Condition

Abstract: A crossbreeding experiment was executed between three breeds were selected three generation for heavy body weight under high temperature condition Sinai (SI) and Rhode Island Red (RI) and Fayoumi breeds. 900 crossing meals from each genotype were recorded singular body weight and body weight gain at hatch, 4, 8 and 12 weeks of age. crosses SI XRI and reciprocal RI x Si significant heaver body weight and body weight gain compared than other crosses and pure breed. On the other hand body weight and body weight g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The increased body weight for Baladi chickens may be due to increase the abdominal fat or oviduct weight for hens specially during the final production stages. These results agreed with the results of Radwan and Mahrous (2018a) who indicated that the lowest body weight was recorded in Fayoumi pure line chickens compared with Sinai chicken strain. Also, the results of Nowier et al, (2018) who showed that the body weight for Rod Island Red chickens was significantly heavier than those of Fayoumi and White Leghorn chickens strains.…”
Section: Effect Of Strainsupporting
confidence: 92%
“…The increased body weight for Baladi chickens may be due to increase the abdominal fat or oviduct weight for hens specially during the final production stages. These results agreed with the results of Radwan and Mahrous (2018a) who indicated that the lowest body weight was recorded in Fayoumi pure line chickens compared with Sinai chicken strain. Also, the results of Nowier et al, (2018) who showed that the body weight for Rod Island Red chickens was significantly heavier than those of Fayoumi and White Leghorn chickens strains.…”
Section: Effect Of Strainsupporting
confidence: 92%
“…Significant differences between the local and commercial strains of chickens for body weight and egg traits were supported in the literature [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 81%
“…Crossbreeding could be used to establish broad genetic basis for the development of new strains or lines and to find superior crossbreds. Some Egyptian studies have shown significant (P≤0.05 and P≤0.01) direct genetic and maternal effects on growth traits at different ages of chickens (e.g., Aly and Abou El-Ella 2005;Saadey et al, 2008;Abd El-A'al 2009;Amin et al, 2013;Amin 2015;Khattab 2014;Mahmoud and El-Full 2014;Radwan and Mahrous 2018;Saleh et al, 2020a&b). In most of these studies, crossing local breeds of chickens with local and/or exotic ones was generally associated with the existence of considerable heterotic effects on growth traits (Saadey et al, 2008;El-Tahawy 2020;Soliman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In most of these studies, crossing local breeds of chickens with local and/or exotic ones was generally associated with the existence of considerable heterotic effects on growth traits (Saadey et al, 2008;El-Tahawy 2020;Soliman et al, 2020). Also, several Egyptian reports (e.g., Iraqi et al, 2002;Abou El-Ghar et al, 2007;Roshdy et al, 2007;Saadey et al, 2008;Abd El-A'al, 2009;Iraqi et al, 2011;Taha and Abd El-Ghany 2013;Amin 2015;Radwan and Mahrous 2018;Saleh et al, 2020a&b) have confirmed the superiority of crossbreds over the purebreds regarding body weights and weight gains at different ages. Khattab (2014) reported that estimates of maternal heterosis for body weights were positive and mostly significant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation